1997
DOI: 10.2307/30141512
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Workers' Attitudes and Compliance with Universal Precautions: Gender, Occupation, and Specialty Differences

Abstract: Jeffe, Donna B.; Sunita, Mutha; L'Ecuyer, Paul B.; Kim, Lynn E.; Singal, Renee B.; Evanoff, Bradley A.; and Fraser, Victoria J., "Healthcare workers' attitudes and compliance with universal precautions: gender, occupation, and specialty differences". Infection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…Studies suggests that non‐compliance with the precautions is affected by different factors, such as age, level of training, experience in using UP, knowledge, attitudes and practice patterns (Young et al. 1996, Jeffe et al. 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies suggests that non‐compliance with the precautions is affected by different factors, such as age, level of training, experience in using UP, knowledge, attitudes and practice patterns (Young et al. 1996, Jeffe et al. 1997).…”
Section: Introductionmentioning
confidence: 99%
“…A study in an obstetric setting found that 10% of nurses were unfamiliar with the UP, whereas 38% regarded them as unnecessary and 79% believed they interfered with the patient–midwife relationship (Bauer 1991). Jeffe et al. (1997) found that a greater percentage of surgeons than surgical nurses disagreed with the need to double glove for all invasive procedures, as they held the belief that there is a low prevalence of blood‐borne disease, where they work.…”
Section: Introductionmentioning
confidence: 99%
“…Although, standard precautions were introduced in the 1980s, research continues to report less than 100% compliance among health care professionals with measures demonstrated to decrease disease transmission 5–15 5. The consequences of an occupational exposure to bloodborne pathogens extend beyond transmission of infection.…”
Section: Occupational Exposure In the Ormentioning
confidence: 99%
“…Hospital de Câncer de Barretos, Barretos-SP, 2011 ................................................ 51 Tabela 12 -Distribuição das respostas dos profissionais de enfermagem que sofreram exposição ocupacional a material biológico sobre conhecimento das condutas pós-exposição segundo o tipo de conduta adotada. Hospital de Câncer de Barretos, Barretos-SP, 2011 (CDC, 2008;DO et al, 2003;JEFFE et al, 1997;PURO;PETROSILLO;IPPOLITO, 1995;RAPPARINI, 2006).…”
Section: Tabela 4 -unclassified
“…Apesar de as PP serem reconhecidas pela comunidade científica (CLARKE et al, 2002;HENDERSON, 2003) como uma das mais importantes e eficazes medidas preventivas pré-exposição à material biológico, autores têm apontado que sua aplicação na prática de trabalho permanece abaixo do ideal (GERSHON et al, 1995;JEFFE et al, 1997;KIM et al, 1999;PEREIRA et al, 1999 (CDC, 2005;LEE;HENDERSON, 2001;MEDEIROS et al, 2007;WANG et al, 2000).…”
Section: Tabela 5 -unclassified